Transient Receptor Potential Cation Channel Subfamily Vanilloid 4 and 3 in the Inner Ear Protect Hearing in Mice - Wang, Shengnan; Geng, Qiaowei; Huo, Lifang; Ma, Yirui; Gao, Yiting; Zhang, Wei; Zhang, Hailin; Lv, Ping; Jia, Zhanfeng (Frontiers in Molecular Neuroscience, 2019)
The transient receptor potential cation channel vanilloid type (TRPV) 3, is a member of the TRPV subfamily that is expressed predominantly in the skin, hair follicles, and gastrointestinal tract. It is also distributed in the organ of Corti of the inner ear and colocalizes with TRPV1 or TRPV4, but its role in auditory function is unknown. In the present study we demonstrate that TRPV3 is expressed in inner hair cells but mainly in cochlear outer hair cells (HCs) in mice, with expression limited to the cytoplasm and not detected in stereocilia. We compared the number of HCs as well as distortion product otoacoustic emissions and auditory brainstem response thresholds between TRPV3 knockout (V3KO) and wild-type (V3WT) mice and found that although most mutants (72.3%) had normal hearing, a significant proportion (27.7%) showed impaired hearing associated with loss of cochlear HCs. Compensatory upregulation of TRPV4 in HCs prevented HC damage and kanamycin-induced hearing loss and preserved normal auditory function in most of these mice. Thus, TRPV4 and TRPV3 in cochlear HCs protect hearing in mice; moreover, the results suggest some functional redundancy in the functions of TRPV family members. Our findings provide novel insight into the molecular basis of auditory function in mammals that can be applied to the development of strategies to mitigate hearing loss.